2000
DOI: 10.1007/s004670050038
|View full text |Cite
|
Sign up to set email alerts
|

Role of transplant induction therapy on recurrence rate of focal segmental glomerulosclerosis

Abstract: Individuals with focal segmental glomerulosclerosis (FSGS) are at risk for recurrence of disease following renal transplantation. The rate of recurrence has been estimated to range from 20% to 30%. The factors associated with an increased probability of recurrence are not known, although the rapidity of progression of disease, age at onset, and the presence of diffuse mesangial proliferation in the native kidney have all been implicated. We analyzed the data from 35 patients with FSGS who received 37 renal tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 32 publications
(53 reference statements)
3
30
1
Order By: Relevance
“…Post-transplant recurrence of FSGS continues to have a high prevalence rate, estimated to range from 20% to 50% and appears to be increasing in some centers [16,17]. Raafat et al [16] first reported a significant increase in FSGS recurrence from 11% in patients without induction therapy to 53% and 88%, respectively, in those treated with ALG and anti-thymocyte polyclonal antibody (AT-GAM).…”
Section: Discussionmentioning
confidence: 98%
“…Post-transplant recurrence of FSGS continues to have a high prevalence rate, estimated to range from 20% to 50% and appears to be increasing in some centers [16,17]. Raafat et al [16] first reported a significant increase in FSGS recurrence from 11% in patients without induction therapy to 53% and 88%, respectively, in those treated with ALG and anti-thymocyte polyclonal antibody (AT-GAM).…”
Section: Discussionmentioning
confidence: 98%
“…Plasmapheresis Plasma-based treatments, primarily plasmapheresis, have been used as a first-line treatment for FSGS and for recurrent FSGS after transplantation for nearly 20 years [5,[46][47][48][49][50][51][52][53][54][55][56][57][58][59]. The results of select studies performed since the year 2000 with larger numbers of patients are summarized in Table 2.…”
Section: Treatmentmentioning
confidence: 99%
“…There does not appear to be any consistent effect of gender (282,286), the type of prophylactic immunosuppression used (276,277,279) or the time spent on renal replacement therapy before transplantation (276). In one uncontrolled study the use of antibody induction therapy was associated with a higher incidence of recurrent FSGS (287). There is also a hereditary form of FSGS (294); in this form, FSGS does not appear to recur as often after transplantation (294,295).…”
Section: The Evaluation Of Renal Transplant Candidates: Clinical Pracmentioning
confidence: 99%